Perlindungan Hak Merek yang Terjadi Antara Gudang Garam Dengan Gudang Baru Atas Adanya Unsur Persamaan Pada Pokoknya (Analisis Putusan Mahkamah Agung Nomor 119PK/Pdt.Sus-HKI/Merek/2017) - Mohammad Rezki Septiawan; Eko Rial Nugroho (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The aim of writing this research is to determine the procedure for determining the criteria for similarities in the main elements of a well-known brand between Gudang Garam and Gudang Baru and to determine the impact of the Supreme Court Judge's considerations in deciding the dispute between the Gudang Garam and Gudang Baru brands in Supreme Court Decision Number 119PK/Pdt.Sus-HKI /2017. The research method used in this writing is normative legal research with primary legal materials, namely the Civil Code, Law Number 20 of 2016 concerning Marks and Geographical Indications; and Minister of Law and Human Rights Regulation Number 67 of 2016 concerning Trademark Registration, Minister of Law and Human Rights Regulation Number 12 of 2021 concerning Amendments to Ministerial Regulation Number 67 of 2016 concerning Mark Registration. This is motivated by Intellectual Property Rights (IPR) covering various elements, such as trademarks, geographical indications and product designs, which protect human creativity. In Indonesia, brands have developed since the 19th century, from producer identification to quality markers and psychological symbols. A registered trademark gives its owner exclusive rights and protects against infringement. Cases like PT. Gudang Garam vs. PR. Jaya Makmur shows the importance of brand protection and legal decisions in preventing misuse. The conclusion of this research is that the visual and conceptual similarities of the Gudang Garam and Gudang Baru brands mislead consumers. The Supreme Court's decision strengthens Gudang Garam's ownership of 79 registration numbers since 1979 in class 34. Strong evidence is needed for the plaintiff and improvements in the judge's consideration for a strong legal basis, especially when the trademark is being registered.